IMPROVING READING COMPREHENSION USING MIND MAPPING CONCEPT - Noor Chairani (Universitas Negeri Padang, 2015)
In the global era, English is needed as one of international languages. English is learned by many people in the world to access inJormalion and lo convey or communicate ideas to solve problems of life. Reading as a basic skill of languge has to be mastered because reading comprehension is crucial for academic success to achieve the purpose of learning language. A strategy is needed to increase learners' reading comprehension actively and practically enable learners to understand a text comprehensively. Learners who do not know, or use appropriale strategies in language learning especially in reading comprehension often learn passively and slowly. There are some factors that may influence the learners' success in their reading comprehension. One of them is applying a technique in their reading activity. Mind-mapping concept is considered as one of techniques hopefully used to improve learners' reading comprehension. The strategy makes learners to become active because they are involved independently in teaching and learning process. The more learners are involved in learning and teaching process, the more they can comprehend the materials learned. The mind-mapping concept can be applied to improve learners' reading comprehension ability to help them understand information or get inputs from the texts. By applying mind mapping concept, learners can understand and remember the contents of text easily.